Prominent renal complications associated with MMACHC pathogenic variant c.80A > G in Chinese children with cobalamin C deficiency - Liu, Xiaoyu; Xiao, Huijie; Yao, Yong; Wang, Suxia; Zhang, Hongwen; Zhong, Xuhui; Yang, Yanling; Ding, Jie; Wang, Fang (Frontiers in Pediatrics, 2023)
Objective: CblC deficiency, the most common cobalamin metabolic abnormality, is caused by pathogenic variants in the MMACHC gene. The renal complications of this disease have been described only in a small number of cases. The aim of the present study was to better delineate renal phenotype and genetic characteristics in Chinese children with cblC defect. Methods: Children with cblC deficiency who manifested as kidney damage were enrolled. Clinical, renal pathological and genetic data was reviewed in detail. Results: Seven cases were enrolled. Ages at disease onset ranged from 9 months to 5 years. All patients presented with hematuria and proteinuria; 2/7 cases presented with nephrotic syndrome. Renal dysfunction was observed in 4/7 cases. Renal biopsy was performed in 5/7 cases, and all of them had renal thrombotic microangiopathy. Macrocytic anemia was detected in all 7 patients. Six out of seven cases had hypertension, and 2/7 cases presented with pulmonary hypertension. Two of them had mild intellectual disability, and one of them suffered with epilepsy. Increased urine methylmalonic acid and plasma homocysteine were detected in 7 cases, while 2 patients had normal level of urine methylmalonic acid at the initial evaluation. After diagnosis, all 7 cases were treated with hydroxycobalamin IM. Six cases were seen for a follow up of 3-8 years. After treatments, anemia was the first to be recovered followed by proteinuria. Renal function recovered after one year in 2 cases, whereas patient 2 progressed to stage 2 chronic kidney disease 13 years after onset. While a case presented with end stage kidney disease because of late diagnosis, and one case died 3 months after disease onset due to giving up treatment. Three MMACHC pathogenic variants c. 80A>G (8/14), c. 609G>A (4/14), and c. 658_660delAAG (2/14) were detected in all the 7 children. Conclusion: MMACHC variant c.80A>G may be associated with prominent renal complications in Chinese cblC patients. Macrocytic anemia and hyperhomocysteinemia are useful clues for patients with hematuria and proteinuria caused by cblC defect. The most frequent renal pathological manifestation is thrombotic microangiopathy. Early diagnosis and treatment resulted in improvement of renal and hematological signs.